2006
DOI: 10.1002/hep.20993
|View full text |Cite
|
Sign up to set email alerts
|

The Hyperdynamic Circulation of Chronic Liver Diseases: From the Patient to the Molecule

Abstract: The hyperdynamic circulatory syndrome observed in chronic liver diseases is a great example of research that originated from clinical observations and progressed in the last 50 years from the patient to the experimental laboratory. Our knowledge has evolved from the patient to the molecule, using experimental models that serve as a source for understanding the complex pathophysiological mechanisms that govern this complex syndrome. We now know that progressive vasodilatation is central to the detrimental effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
442
0
20

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 540 publications
(473 citation statements)
references
References 128 publications
(145 reference statements)
11
442
0
20
Order By: Relevance
“…Usually, the HVPG ranges from 1 to 5 mmHg, becoming clinically significant when it reaches 10 mmHg [6]. In clinical practice, an increase in HPVG values of at least 12 mmHg is usually associated with the presence of esophageal varices [2,6]. Progressing through the stages of cirrhosis, there is a wide development of a network of collateral vessels, which bypassing the liver, creates communication between the portal vein and the systemic circulation.…”
Section: Hemodynamic Changes Contributing To Hyperdynamic Syndromementioning
confidence: 99%
See 1 more Smart Citation
“…Usually, the HVPG ranges from 1 to 5 mmHg, becoming clinically significant when it reaches 10 mmHg [6]. In clinical practice, an increase in HPVG values of at least 12 mmHg is usually associated with the presence of esophageal varices [2,6]. Progressing through the stages of cirrhosis, there is a wide development of a network of collateral vessels, which bypassing the liver, creates communication between the portal vein and the systemic circulation.…”
Section: Hemodynamic Changes Contributing To Hyperdynamic Syndromementioning
confidence: 99%
“…The hyperdynamic syndrome (HS) is a consequence of cirrhosis of varying etiologies [1,2]. This syndrome has been defined by high cardiac output, increased heart rate and total blood volume, reduced total systemic vascular resistance, and low, normal or decreased arterial pressure [1][2][3].…”
Section: Introductionmentioning
confidence: 99%
“…Nitric oxide (NO), tumor necrosis factoralfa (TNF-α), endocannabinoids, adrenomedullin, calcitonin gene-related peptide (CGRP), and carbon monoxide (CO) are the most important mediators in this field [13,14]. On the contrary, a concomitant activation of the sympathetic nervous system and the renin-angiotensin aldosterone system (RAAS) (noradrenaline, neuropeptide-Y, endothelin-1, angiotensin II, and vasopressin) has been observed [15,16] (Fig. 1).…”
Section: Role Of the Vascular Tone In The Genesis Of Cirrhotic Cardiomentioning
confidence: 99%
“…Hyperdynamic circulation stands out among the splanchnic and systemic alterations related to portal hypertension [1,[11][12][13][14][15]. It has been suggested that the splanchnic and systemic vasodilation is the initial step leading to the hyperdynamic syndrome or progressive vasodilatory syndrome [12,16]. Multiple organ failure in portal hypertensive chronic liver disease is in large part attributeable to this syndrome [14,16].…”
Section: The Ischemia-reperfusion Phenotype: the Hydroelectrolitic Chmentioning
confidence: 99%
“…nance of an inflammatory response. First, the pathological increase of the portal pressure that occurs in the hyperdynamic splanchnic circulation could favor a disturbed splanchnic venous flow with shear stress mediated by non-laminar flow [12]. The disturbed or non-laminar flow with associated reciprocating low shear stress has profound effects on the biology of the vascular wall, particularly the vascular endothelium, and could stimulate inflammation [17,18].…”
Section: The Ischemia-reperfusion Phenotype: the Hydroelectrolitic Chmentioning
confidence: 99%